Herpetic whitlow in a child with AIDS: the importance of Tzanck test in the diagnosis - Ricardo Barbosa Lima; Mariana de Almeida Pinto Borges; Luciana Ferreira de Araújo; Carlos José Martins (Anais Brasileiros de Dermatologia, 2021)
Abstract Herpetic whitlow is a viral infection of the fingers caused by the herpes simplex virus. The disease has a bimodal age distribution, affecting children under 10 years of age and young adults between 20 and 30 years old. It can be easily mistaken for panaritium or bacterial cellulitis. In patients with AIDS, atypical, chronic and recurrent ulcerated lesions occur. The Tzanck test allows a quick and low-cost diagnosis of herpes simplex virus infection. The authors report the case of a child with AIDS with painful finger ulcers in which the diagnosis was confirmed by the Tzanck test.